The midnight lock eaudiobook - Deaver, Jeffery (Lincoln Rhyme, 2021)
The "master of ticking-bomb suspense" ( People ) Jeffery Deaver delivers the latest thriller featuring his beloved protagonists Lincoln Rhyme and Amelia Sachs as they search for a criminal whose fascination with breaking locks terrorizes New York City. A woman awakes in the morning to find that someone has picked her apartment’s supposedly impregnable door lock and rearranged personal items, even sitting beside her while she slept. The intrusion, the police learn, is a message to the entire city of carnage to come. Lincoln Rhyme and Amelia Sachs are brought in to investigate and soon learn that the sociopathic intruder, who calls himself "the Locksmith,” can break through any lock or security system ever devised. With more victims on the horizon, Rhyme, Sachs and their stable of associates must follow the evidence to the man’s lair… and discover his true mission. Their hunt is interrupted when an internal investigation in the police force uncovers what seems to be a crucial mistake in one of Rhyme's previous cases. He’s fired as a consultant for the NYPD and must risk jail if he investigates the Locksmith case in secret.   The Midnight Lock is a roller-coaster read that takes place over just a few days’ time, features surprise after surprise and offers a fascinating look at the esoteric world of lockpicking.